Arabidopsis Raf‐like kinases act as positive regulators of subclass III SnRK2 in osmostress signaling. (18th April 2020) - Katsuta, Shohei; Masuda, Goro; Bak, Hyeokjin; Shinozawa, Akihisa; Kamiyama, Yoshiaki; Umezawa, Taishi; Takezawa, Daisuke; Yotsui, Izumi; Taji, Teruaki; Sakata, Yoichi
SUMMARY: Given their sessile nature, land plants must use various mechanisms to manage dehydration under water‐deficit conditions. Osmostress‐induced activation of the SNF1‐related protein kinase 2 (SnRK2) family elicits physiological responses such as stomatal closure to protect plants during drought conditions. With the plant hormone ABA receptors [PYR (pyrabactin resistance)/PYL (pyrabactin resistance‐like)/RCAR (regulatory component of ABA receptors) proteins] and group A protein phosphatases, subclass III SnRK2 also constitutes a core signaling module for ABA, and osmostress triggers ABA accumulation. How SnRK2 is activated through ABA has been clarified, although its activation through osmostress remains unclear. Here, we show that Arabidopsis ABA and abiotic stress‐responsive Raf‐like kinases (AtARKs) of the B3 clade of the mitogen‐activated kinase kinase kinase (MAPKKK) family are crucial in SnRK2‐mediated osmostress responses. Disruption of AtARKs in Arabidopsis results in increased water loss from detached leaves because of impaired stomatal closure in response to osmostress. Our findings obtained in vitro and in planta have shown that AtARKs interact physically with SRK2E, a core factor for stomatal closure in response to drought. Furthermore, we show that AtARK phosphorylates S171 and S175 in the activation loop of SRK2E in vitro and that At ark mutants have defects in osmostress‐induced subclass III SnRK2 activity. Our findings identify a specific type of B3‐MAPKKKs as upstream kinases of subclass III SnRK2 in Arabidopsis. Taken together with earlier reports that ARK is an upstream kinase of SnRK2 in moss, an existing member of a basal land plant lineage, we propose that ARK/SnRK2 module is evolutionarily conserved across 400 million years of land plant evolution for conferring protection against drought. Significance Statement: Here, we show that Arabidopsis ABA and abiotic stress‐responsive Raf‐like kinases (AtARKs) belonging to the B3 clade of the mitogen‐activated kinase kinase kinase family play a crucial role in Arabidopsis drought responses, such as stomatal closure, through phosphorylation‐mediated activation of subclass III SNF1‐related protein kinase 2 (SnRK2) partly in an abscisic acid‐independent manner. Our findings indicate that ARK is a novel component of osmostress signaling that connects osmosensing with SnRK2 activation.